Economic of Small-Scale Hand Line Fishery Fleet Production Based On Driving Power in Every Season in The Small Island Park Conservation Area, Southeast Maluku Regency - Picaulima, Simon Marsholl; Makailipessy, Marvin Mario; Thenu, Imanuel Musa (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
The economic benefits of hand line production activities carried out by small fishermen utilizing some inputs to produce high economic value output each season in the Kei Kecil small island park (TPK) conservation area differ according to the driving power. Production cost efficiency, effectiveness of production results, and business profits are very important for the sustainability and development of small-scale hand-line fisheries. This study aims to analyze the economics of small-scale hand line production based on the driving power in each season in the TPK Kei conservation area. The type of data needed is primary and secondary data, and the collection method used is triangulation. The analysis used includes analysis of business profits, production cost efficiency, and effectiveness of production results. The results of the analysis show that the production of hand line carried out in the TPK Kei Kecil conservation area in each season is more efficient and effective in the hand line fishing fleet that uses hand line rowing and the highest business profit is the hand line fishing fleet that uses ketinting driving power. The production of small-scale hand lines in the TPK Kei conservation area is small in each season efficiently, effectively, and profitably.